2022
DOI: 10.21608/asnj.2022.140671.1386
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice Regarding COVID-19 and Perceived Barriers to Infection Control among Family Health Center and Hospital Nurses in Alexandria

Abstract: In the fight against the unique and potentially lethal Coronavirus 2019 (COVID-19) pandemic, nurses are at the forefront of the medical community. Inadequate information and inappropriate attitudes among nurses can directly impact behaviors, resulting in poor infection control and disease spread. Aim of the research: This research aimed to compare the knowledge, attitude, and practice toward COVID-19 and the observed difficulties toward infection control between nurses in Family Health Center sand hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…21,22 As most nurses at position level N have only recently graduated from schools and are relatively young, it naturally follows that they have a high acceptance of, and strong usage intention for, new technologies. However, Mamdouh and Mohammed 23 established that the acceptance of electronic information systems is higher among nurses with 10 or more years of relevant work experience than among those with less than 10 years of relevant work experience. This discrepancy may be attributed to the differences between the service units investigated in the studies concerned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 As most nurses at position level N have only recently graduated from schools and are relatively young, it naturally follows that they have a high acceptance of, and strong usage intention for, new technologies. However, Mamdouh and Mohammed 23 established that the acceptance of electronic information systems is higher among nurses with 10 or more years of relevant work experience than among those with less than 10 years of relevant work experience. This discrepancy may be attributed to the differences between the service units investigated in the studies concerned.…”
Section: Discussionmentioning
confidence: 99%
“…The above observations are similar to the report by Aldosari et al, 32 which revealed that 52.3% of nurses acknowledged the usefulness of EMR systems for clinical work and 40.4% strongly agreed to integrate EMR systems into routine work. Mamdouh and Mohammed 23 showed that 69% of nurses believed that the use of computer graphics can help improve clinical records; 49.5% stated that timely use of electronic files can improve the quality of patient care and reduce the nurses' workloads, and 60.3% acknowledged that electronic records can save paperwork. The computer graphics of the ACLS electronic information system developed by our hospital simplified user guidance, which not only allowed for the immediate recoding of resuscitation procedures but also saved time usually spent compiling paper-based records.…”
Section: Discussionmentioning
confidence: 99%